(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
Computer linguistics or computational linguistics is an interdisciplinary field of linguistics, that analyzes and learns human language using computer methods. This field is gaining rapid popularity in advance with artificial intelligence in developing countries, such as Uzbekistan. This article traces the advances of development of computational linguistics in Uzbekistan and explores main methods, theoretical foundations and the problems it faces today in the world of linguistics.